(untitled) (Medical Forum Monthly, 2024)
Objective: This study aims at comparing complex insulin delivery systems with traditional insulin injection as a means of determining their benefit in enhancing glycemic control and patient satisfaction. Study Design: A Prospective Study. Place and Duration of Study: This study was conducted at the Department of Medicine, HMC, Peshawar from Jan 2023 to July 2023. Methods: A Prospective Study was done in adult diabetic patients (Type 1 and Type 2) of 100 patients over a year. Patients were divided into two groups: Hypoglycemia adverse events were reported by 50 patients using conventional insulin injections and 50 using new technologies such as insulin pumps and new-generation insulin preparations. These outcomes included glycemic control or HbA1c level, incidence of hypoglycemia, and the patient satisfaction level. Results: The pre-study mean age of participants, calculated with 95% confidence, was 46.3 years (SD = 7.8). Insulin delivery systems with more features had better HbA1c outcomes than those with regular injections (mean difference = -1.1%, p = 0.02) than basic ones (mean difference = -0.6%). A moderate decrease in the hypoglycemia episodes by 30% (p = 0.03) was observed for the participants in the advanced group, and 82% of them reported increased satisfaction. Conclusion: Features of modern insulin delivery enhance glycemic control, decrease the risk of hypoglycemia, and increase patient satisfaction compared to conventional approaches and methods. Greater use of these technologies may enhance experiences of diabetes management.